2016
DOI: 10.1007/s40883-016-0019-2
|View full text |Cite
|
Sign up to set email alerts
|

Biologic and Tissue Engineering Strategies for Tendon Repair

Abstract: This review summarizes recent developments in biologic treatments-including growth factors, platelet-rich plasma (PRP), stem cells, and cell-seeded scaffolds-for tendon repair. Growth and differentiation faction-5 (GDF-5), insulin-related growth factor-1 (IGF-1), and basic fibroblast growth factor (bFGF) all improved extracellular matrix (ECM) production and tensile strength of treated tendons; however, no clinical trials were done on GDF-5. Platelet-derived growth factor-BB (PDGF-BB) improved proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 124 publications
(168 reference statements)
0
20
0
Order By: Relevance
“…We proved expediency of using polyethylene terephthalate for fixation of soft tissues, as only this material use allows preserving anatomical structures as much as possible. In addition, in case of extensor apparatus fixation of the knee joint, only in polyethylene terephthalate use, tendon-like tissue is formed in the area of knee ligament attachment [3,11,13,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We proved expediency of using polyethylene terephthalate for fixation of soft tissues, as only this material use allows preserving anatomical structures as much as possible. In addition, in case of extensor apparatus fixation of the knee joint, only in polyethylene terephthalate use, tendon-like tissue is formed in the area of knee ligament attachment [3,11,13,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…These include infections, structural disorders, aseptic instability, local recurrence, and a number of soft tissue lesions [3,8,11,[17][18][19][20][21][22][23][24][25][26]. To further standardize complications, E. R. Henderson et al [8] proposed a classification that was adopted in 2014 by the International Society of Limb Salvage (ISOLS).…”
mentioning
confidence: 99%
“…The effects of mitogenic GFs such as fibroblast growth factor, bFGF, platelet-derived growth factor (PDGF-BB), and differentiation factors such as insulin-like growth factor-1 (IGF-1), growth and differentiation factor-5 (GDF-5), and bone morphogenetic protein-12 (BMP-12) on BMSCs are well known and have been extensively studied. ,, Recently, insulin, which closely resembles IGF-1 was reported as a molecule of interest for differentiating BMSCs into tendon. After identifying optimal dosages of insulin (10 –10 mol/L), via real time polymerase chain reaction (RT-PCR), Western blotting, and immunocytochemical analyses, the authors demonstrated the significant up-regulation of the tendon-related proteins/genes collagen type-I (COL1A1), collagen type-III (COL3A1), scleraxis (Scx), TN-C, decorin, similar to those levels observed in IGF-1, bFGF and GDF-5 administration, demonstrating the potential of insulin in rotator cuff generation (Figure C–G) .…”
Section: Cell Sources For Rotator Cuff Tendons Healingmentioning
confidence: 99%
“…The scar tissue is inferior in mechanical properties due to the predominant presence of type III collagen, whereas healthy tendon tissue mainly consists of type I collagen. An excessive amount of type III collagen results in loosely organized fibrils [ 13 ]. These complications can be avoided by inducing a healing response that is faster than the rate of adhesion and scar tissue formation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%